Robust stall detection of three-phase induction motors using transient-aware current-speed monitoring - Muchlas Muchlas; Herman Dwi Surjono; Tole Sutikno; Barry Nur Setyanto (Institute of Advanced Engineering and Science, 2026)
Reliable stall detection is essential for protecting three-phase induction motors from thermal damage while maintaining uninterrupted industrial operation. Conventional threshold-based protection methods often struggle to distinguish transient overload events from sustained stall conditions, resulting in nuisance trips or delayed fault detection under dynamic operating conditions. This paper proposes a robust transient-aware stall detection framework that combines stator current monitoring, rotor speed monitoring, startup inhibition, adaptive activation logic, and hold-time verification within a lightweight threshold-based decision process. The proposed algorithm was implemented and evaluated using a MATLAB/Simulink model of a three-phase squirrel-cage induction motor under representative operating scenarios, including motor startup, temporary overload, and sustained stall conditions. Simulation results demonstrate that the proposed framework successfully suppresses unnecessary trips during short-duration overloads by allowing the motor to re-accelerate after transient disturbances. Conversely, when abnormal operating conditions persist beyond the predefined hold time, the algorithm reliably identifies an actual stall and activates the protection relay to disconnect the motor. By integrating temporal verification with simultaneous current and speed monitoring, the proposed framework effectively discriminates recoverable transient events from sustained stall conditions while maintaining low computational complexity. These characteristics make the proposed method suitable for practical real-time induction motor protection in industrial automation applications.